Pembinaan Disiplin Kerja Anggota Polri di Polsek Koto Tangah dalam Rangka Meningkatkan Pelayanan kepada Masyarakat - Amanta Zahra; Vionanda Aliza Putri; Melani Fitria Devita Sari; Dewi Rahmawati (Dinasti Research, 2023)
Development of work discipline is important to be carried out by every organization to explore the potential and qualities possessed by someone who works, one of which is by members of the police at the Koto Tangah Police Station. Work discipline actually starts from oneself which then the impact of this discipline can be felt at least by oneself, then by organizations or agencies and also the community. The purpose of this study is to find out and analyze obstacles in improving services to the community at the Koto Tangah Police Station and the solution to these problems then describe and analyze the development of work discipline of police members at the Koto Tangah Police Station in order to improve services to the community. This research was conducted by descriptive qualitative method. Based on this research, it was found that there were several obstacles faced by the Koto Tangah Police in improving services, namely limited personnel, limited budget, and lack of public trust in the police. The development of work discipline of police members at the Koto Tangah Police Station is carried out by conducting various trainings for police members at the Koto Tangah Police Station and the active role of the Koto Tangah Police Chief as a motivator, controling and evaluator of the performance of Koto Tangah Police members in carrying out their duties.